Fulfilling the Rights of Housing Consumers As a Result of Developer's Bankruptcy Decision - Maharini Kerti, Renti; Wicaksana, Arif (KnE Social Sciences, 2022)
The state guarantees the right of every citizen to get a decent living and a place to live as a human being. Consumer rights in the housing sector are regulated in Law Number 8 of 1999 concerning Consumer Protection, Law Number 1 of 2011 concerning Housing and Settlement Areas, and Law Number 20 of 2011 concerning Flats. Consumer rights are the obligation of business actors to fulfill. Bankruptcy is an effort for creditors to fulfill their rights to debtors. In principle, consumers in the housing sector do not want developers to go bankrupt, but on the contrary, bankruptcy is used as a loophole for irresponsible developers to avoid their obligations. The consumer’s position becomes a questionable matter because the consumer’s position is harmed by the bankruptcy decision. In this paper, we will discuss on how is the position of consumers in the housing sector as a result of the bankruptcy decision of the developer and the efforts to fulfill the rights of housing consumers fairly. The research method used is normative with an approach to norms and principles in regulation. The data used is secondary with qualitative data analysis and deductive conclusions. The purpose of this paper is to explain the position of housing consumers on the developer’s bankruptcy decision, and efforts to fulfill consumer rights due to the developer’s bankruptcy decision. The developer’s bankruptcy decision has resulted in housing consumers being concurrent creditors. Efforts that can be taken to fulfill consumer rights are to position consumers as creditors with special rights because of the law based on the Circular Letter of the Supreme Court Number 4 of 2016 and the Decision of the Constitutional Court 21 of 2015, in addition to efforts to file a lawsuit to the district court as well as amendments to bankruptcy regulations and consumer protection. Keywords: bankruptcy, housing, consumer protection